Exploring English as a foreign language students' perceptions and needs of digital competences in a Turkish higher education context - Murat Akbıyık; Didem Koban Koç (Literacy Trek, 2024)
The purpose of this study is to explore the perceptions of college students towards digital competences and how they evaluate their needs for competence in learning and using English as a foreign language (EFL). The participants are 20 students (10 males and 10 females) learning EFL at the school of foreign languages of a private university in İstanbul, Türkiye. Data were collected via a socio-demographic questionnaire and semi-structured interviews. For the analyses of the qualitative data, codes, and themes were determined and organized according to the inductive thematic analysis approach, for which Braun and Clarke's (2006) six-step procedure was followed. The results revealed themes of skills for digitalization, ownership of digital tools, positive attitudes towards digital competences in language education, needs relating to language use and learning: assessment, communication, interaction, resources, information, lessons and teachers, and finally, differences between before and after distance education in terms of digital competences. Compared with the present literature, tertiary level EFL learners have positive views of digital competences that cover widely accepted definitions and perceive their own digital competence levels as sufficient, teachers are perceived as having more digital competence than students. Digital competences are widely used in lessons, extracurricular activities, and assessment-evaluation processes, even though school curricula do not sufficiently prioritise them. They also believe that they need similar digital competences in foreign language education, parallel to literature. Although it has been shown that the school gives students enough opportunity to enhance their digital competences, there are still several suggestions made by the participants to advance their academic and professional goals. Furthermore, it is thought that national higher education policies do not place enough emphasis on this issue. In conclusion, digital competences should be prioritised, according to suggestions made by national policymakers, institution administrators, and university instructors as well as students.